Evaluasi Sudut Tibiofemoral dan Jarak Intermalleolar atau Interkondilar Pada Populasi Dewasa Muda: Sebuah Studi Pendahuluan - Julius Albert Sugianto; Tri Wahyu Martanto; Paulus Rahardjo (Majalah Kedokteran Indonesia, 2018)
Introduction: Clinical measurement of Tibiofemoral (TF) angle and Intermalleolar/Intercondylar (IM/IC) distance are quick, low cost, reliable, and radiation-free way to screen for pathological genu varus/valgum. TF Angle and IM/IC distance varied between countries and races. Meanwhile, research regarding normal TF Angle and IM/IC distance in Indonesia has not been reported before.Aim: To find the average TF angle and IM/IC distance on medical students of Medical Faculty of Airlangga University batch 2013.Methods: Descriptive epidemiologic study were conducted. The data is collected by direct measurement on the sample.Results: We measured 168 students which fulfilled the inclusion criteria. 65% of the samples were 20 years old and 61% of the samples were females. Amongst the samples, 64% had normal BMI, 11% were underweight, and 26% were overweight and obese. Average BMI is 22,9 ± 4,1. The average TF angle were -7,50 ± 3,350 valgum while the average IM/IC distance were -4,4 ± 33,09 mm intermalleolar. Compared to previous studies, there is slight differences in TF angle and IM/IC distance but were comparable.Conclusion: Amongst medical students of Faculty of Medicine Airlangga University, the TF angle and IM/IC distance were comparable to other studies and mostly had valgus angle.